ORGANIZATIONAL BEHAVIOR MANAGEMENT IN REALIZING COMPETENT HUMAN RESOURCES - Tenri Sayu Puspitaningsih Dipoatmodjo; Rizky Inninawa Muhammad; Khaidir Syahrul (Journal Management & Economics Review (JUMPER), 2023)
The Darussalam Paceti (MI) Madrasah Organization did this research on the management of organizational behavior in 2017/2018. This paper explains the organizational behavior of madrasah management in MI in 2017–2018 in terms of human resources, challenges, and solutions. aims of the study 1) Describe the organization's management of madrasah conduct for a full year during the 2017–2018 MI personnel management implementation. 2. Examining Challenges and Their Resolutions The findings of this study show that (1) Madrasah Ibtidaiyah (MI) has been designed; all activities are analyzed or comprise mental abilities, talents, and work experience; and (2) Madrasah Organizational Behavior in the Implementation of Good HR Darussalam Pacet. introduction, excellent manners, neglecting family ties and giving priority to professional accomplishments and talents, academic and extracurricular achievements, and manners. Evolution; to alter behavior through workshops, education, and training in order for changes and improvements to happen. control; There are a number of school activities, student status, infrastructure, teachers, programs, and amenities that take place each month. three stages of court decision-making: monthly breaks, the conclusion of each semester, and the end of the academic year. There is no need for lectures; graduates do not need to be taught; lecturers who do so are not qualified in their disciplines, lack leadership, and receive poor evaluations. the use of academic and nonacademic possibilities in organizational emphasis, training, workshops, and teacher education development.